Francis Baylies papers - Baylies, Francis, 1783-1852.
Correspondence, speech, writings, notes, and other papers relating to chiefly to Baylies's writings on the American Revolution; the Confederation; U.S. Constitution; Alexander Hamilton; and the presidential administrations of George Washington, John Adams, and Thomas Jefferson. Subjects also include the aurora borealis; colony of New Plymouth, Mass.; Massachusetts General Court House of Representatives; voyage of the USS Lexington (Sloop); and the Falkland Islands fisheries dispute. Includes transcripts of Alexander Hamilton's correspondence.
In part, transcripts.
Scholar, diplomat, politician, and historian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John, -- 1735-1826.; Hamilton, Alexander, -- 1757-1804.; Hamilton, Alexander, -- 1757-1804 -- Correspondence; Jefferson, Thomas, -- 1743-1826.; Washington, George, -- 1732-1799.; Massachusetts. -- General Court. -- House of Representatives; United States; Lexington (Sloop); Auroras; Fisheries -- Falkland Islands; Falkland Islands -- History; Massachusetts -- History -- New Plymouth, 1620-1691.; Massachusetts -- Politics and government; United States -- History -- Revolution, 1775-1783.; United States -- History -- Confederation, 1783-1789.; United States -- History -- Constitutional period, 1789-1809.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1789.; United States -- Politics and government -- 1789-1809.; Diplomats; Historians; Politicians; Scholars